2000
DOI: 10.1016/s1472-6483(10)61988-8
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome abnormalities in 1255 cleavage-stage human embryos

Abstract: The relationship was examined between chromosome abnormalities in cleavage stage human embryos and maternal age, embryo morphology and development rate. Embryos that were classified as suboptimal for transfer from patients undergoing IVF treatment were disaggregated, and all or most of their cells were fixed for analysis by fluorescence in-situ hybridization. Chromosomes X, Y, 13, 18 and 21, and in some instances 16 were examined. A total of 731 non-viable embryos was analysed. An increase in chromosome abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
92
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(100 citation statements)
references
References 25 publications
5
92
0
3
Order By: Relevance
“…However, morphology alone only poorly predicts potential chromosomal abnormalities in embryos selected for transfer. Numerous studies show a significant proportion of aneuploid embryos are capable of achieving the highest morphology score [1,[8][9][10][11][12] and there is no clear distinction made between chromosomally normal and abnormal embryos by morphology assessment alone [13]. In most recent studies of good prognosis patients, aneuploidy is reported to be as high as 44.9 % of good quality blastocysts biopsied [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, morphology alone only poorly predicts potential chromosomal abnormalities in embryos selected for transfer. Numerous studies show a significant proportion of aneuploid embryos are capable of achieving the highest morphology score [1,[8][9][10][11][12] and there is no clear distinction made between chromosomally normal and abnormal embryos by morphology assessment alone [13]. In most recent studies of good prognosis patients, aneuploidy is reported to be as high as 44.9 % of good quality blastocysts biopsied [14].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Ya pı lan ça lış ma lar da, ile ri an ne ya şı ile anöp lo i di; em bri yo nel ge li şim dur ma sı ile po lip lo i di ve ya vaş ge li şim ile post-ma yo tik kro mo zom ano ma li le ri ara sın da doğ ru dan iliş ki gös te ril miş tir. 4,9 Sperm ler de ya pı lan ça lış ma lar, cin si yet kromo zom la rı ile 21 ve 22 no lu kro mo zom la ra ait anoma li le ri nin sık lı ğı nın yük sek ol du ğu nu gös ter miş-tir. [10][11][12][13][14] Ma yo tik bo zuk luk gös te ren ol gu lar in ce lendi ğin de ise sperm dip lo i di si nin en sık rast la nan kro mo zom bo zuk lu ğu ol du ğu gös te ril miş tir.…”
unclassified
“…Anöp lo i di nin ne de ni an ne ye bağ lı fak tör ler ola bile ce ği gi bi prob lem ba ba kay nak lı da ola bil mek tedir. 3,9,[29][30][31] Bu ça lış ma da, er ken dö nem de bu lu nan em bri yo lar da ge li şi min dur ma sı nı açık la ma ya ça-lış mak üze re em bri yo nun ken di sin de ve ba ba dan el de edi len sperm ler de araş tır ma plan lan mış tır.…”
unclassified
“…This improvement in embryo quality is not necessarily related to the number of embryos, and could be explained by the increase of embryos with chromosomal abnormalities in this group. An increase in embryo chromosomal abnormalities in women with advanced age has been reported [22]. This increase in abnormal embryos is related with the increase of chromosomal abnormalities in the oocytes of these patients [23].…”
Section: Discussionmentioning
confidence: 91%